Menu Close

arctan-x-x-dx-




Question Number 62908 by aliesam last updated on 26/Jun/19
∫((arctan(x))/x)dx
arctan(x)xdx
Commented by mathmax by abdo last updated on 26/Jun/19
 for all x from R    u→((arctanu)/u)is integrable on ]0,x]let f(t) =∫_0 ^x  ((arctan(tu))/u)du  we have f^′ (t) =∫_0 ^x  arctan(tu)du =_(by parts)    [u arctan(tu)]_(u=0) ^(u=x)  −∫_0 ^x  u(t/(1+t^2 u^2 )) du  =x arctan(tx)−(1/(2t)) ∫_0 ^x    ((2t^2 u)/(1+t^2 u^2 )) du  =xarctan(tx)−(1/(2t))[ ln(1+t^2 u^2 )]_(u=0) ^(u=x)  =xarctan(tx)−(1/(2t))ln(1+t^2 x^2 ) ⇒  f(t) =∫_0 ^t   x arctan(ux)du −∫_0 ^t  ((ln(1+x^2 u^2 ))/(2u)) du +C  ⇒  ∫_0 ^x  ((arctan(u))/u) du =f(1) =x∫_0 ^1  arctan(ux)du−∫_0 ^1  ((ln(1+x^2 u^2 ))/(2u)) du +C  x=0 ⇒C =0 ⇒∫_0 ^x  ((arctan(u))/u) du=x ∫_0 ^1  arctan(ux)du−∫_0 ^1  ((ln(1+x^2 u^2 3)/(2u)) du  ...be continued....
forallxfromRuarctanuuisintegrableon]0,x]letf(t)=0xarctan(tu)uduwehavef(t)=0xarctan(tu)du=byparts[uarctan(tu)]u=0u=x0xut1+t2u2du=xarctan(tx)12t0x2t2u1+t2u2du=xarctan(tx)12t[ln(1+t2u2)]u=0u=x=xarctan(tx)12tln(1+t2x2)f(t)=0txarctan(ux)du0tln(1+x2u2)2udu+C0xarctan(u)udu=f(1)=x01arctan(ux)du01ln(1+x2u2)2udu+Cx=0C=00xarctan(u)udu=x01arctan(ux)du01ln(1+x2u232udubecontinued.

Leave a Reply

Your email address will not be published. Required fields are marked *